Highlights of the LINEAR survey. Issue 67 (17th July 2015) - Palaversa, L.
Abstract : Lincoln Near-Earth Asteroid Research asteroid survey (LINEAR) observed proximately 10, 000 deg 2 of the northern sky in period roughly from 1998 to 2013. Long baseline of observations combined with good cadence and depth (14.5 < r SDSS < 17.5) provides excellent basis for investigation of variable and transient objects in this relatively faint and underexplored part of the sky. Details covering the repurposing of this survey for use in time domain astronomy, creation of a highly reliable catalogue of approximately 7, 200 periodically variable stars (RR Lyrae, eclipsing binaries, SX Phe stars and LPVs) as well as search for optical signatures of exotic transient events (such as tidal disruption event candidates), are presented.